Multi-taxa referential of a modern Eurasian Eagle-Owl (Bubo bubo) aerie. (August 2020) - Lebreton, Loïc; Bailon, Salvador; Guillaud, Emilie; Testu, Agnès; Perrenoud, Christian
Highlights: First multi-taxa referential of bone remains on a great eagle owl aerie. Comparative analyses between birds, lagomorphs, micromammals, herpetofauna and fishes. Valuable data to determine the main accumulator of small vertebrates in archaeological sites. Abstract: Small vertebrates on archaeological sites are generally the result of predation from different accumulator agents. Depending on their hunting habits, these agents can bias palaeobiodiversity representation; therefore, before undertaking any palaeoenvironmental analysis, it is essential to identify them. Multi-taxa analysis allows better identification of the main accumulator, but the lack of modern referentials is, for now, significantly limiting. The main goal of this study was to set up a comparative tool for small vertebrate taxa and to complete the existing referentials. We analyzed a Eurasian Eagle-Owl ( Bubo bubo ) accumulation – which provided the remains of thousands of rodents, lagomorphs, birds, amphibians, squamates and fishes – n order to study taxonomic composition, skeletal representation, digestion and fragmentation. We then compared these results with the available referentials for different taxa and discussed the use of different variables to better characterize such accumulations. We also present an original taphonomical method to study snakes vertebrae.